(untitled) (Rupandehi Campus Journal, 2025)
This study examines the Silk Road through the lens of religious and cultural exchange. Rather than focusing solely on trade, the paper explores how diverse communities maintained peaceful relations through the exchange and assimilation of cultures, religions, and ideas. Using qualitative methods document and narrative analysis it delves into the historical context and enduring significance of this trans-Eurasian route. The study highlights the diffusion of religious beliefs, art, and cultural practices, positioning the Silk Road as a foundational network that fostered unity and connectivity among ancient civilizations. It also examines the travel culture that helped link distant regions and promoted intercultural dialogue, offering insights relevant to addressing today’s global tensions.